Pengaruh Paparan Ekstrak Biji Klabet (Trigonella foenum-graecum L.) Terhadap Kadar Hemoglobin, Indeks Hepatosomatik dan Kadar Protein Hepar Tikus Putih (Rattus norvegicus L.) - Rofiatul Adawiyah Putri; Agung Janika Sitasiwi; Kasiyati Kasiyati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
ABSTRACT Fenugreek is one of the herbal plants whose seeds contain flavonoid antioxidant compounds, essential amino acids and minerals but their effect on liver function has not been tested. This study consisting of 4 treatment groups, namely P0 (white rats were given aquadest), P1 (white rats were given fenugreek seed extract at dose of 500 mg/kg BW), P2 (white rats were given fenugreek seed extract at dose of 1000 mg/kg BW), and P3 (white rats given fenugreek seed extract at dose of 1500 mg/kg BW). Statistical analysis test used Kruskal Wallis and continued with Mann Whitney test. The results showed that the administration of fenugreek seed extract on the highest hepatosomatic index was found in research rats treated with a dose of 500 mg/kg BW, the highest hemoglobin levels were found in research rats treated with a dose of 1500 mg/kg BW and the highest liver protein levels were found in research rats. treated with a dose of 500 mg/kg BW. The conclusion of this study was that exposure to fenugreek seed extract was able to maintain liver function by showing the value of hepatosomatic index, hemoglobin and liver protein levels in white rats.